Significance of sulfur in heat stressed cluster bean (Cymopsis tetragonoloba L. Taub) genotypes: responses of growth, sugar and antioxidative metabolism. Issue 2 (28th January 2017) - Mobin, Mohammad; Khan, Mohammad Nasir; Abbas, Zahid Khorshid; Ansari, Habib Rahman; Al-Mutairi, Khalid Awad
ABSTRACT: A sand culture experiment was carried out to study the effects of sulfur deprivation on heat stress tolerance of two cluster bean ( Cymopsis tetragonoloba L. Taub) cultivars (GC-1 and Pusa Nau Bahar (PNB)). Three weeks old sulfur-starved and sulfur-supplemented plants were subjected to heat stress (45°C/35°C) treatment for 24 h. Total dry weight, chlorophyll content, Chlorophyll a:b ratio, electrolyte leakage, malondialdehyde (MDA) accumulation, H2 O2 content, sugar, glucose-6-phosphate (G-6-P), fructose-6-phosphate (F-6-P), ascorbate and glutathione concentrations and antioxidant enzyme activity (superoxide dismutase (SOD) and catalase (CAT)) were monitored, at the end of the heat stress treatment. Heat stress enhanced and sulfur starvation depleted the contents of sugar metabolites, but the accumulation of sugar, G-6-P and F-6-P were not related with heat stress tolerance. Antioxidant enzyme activities of SOD and CAT were influenced significantly more by sulfur starvation than heat stress. The results showed that under heat stress, the addition of sulfur helps to mitigate the oxidative damage in both the cultivars. However, GC-1 was more heat tolerant as it was characterized by significantly higher total dry weight, chlorophyll content, ascorbate and glutathione content and lower H2 O2, MDA, electrolyte leakage than PNB.